Synthesis of 3-Thia-1-dethiacephems via Regioselective Iodocyclization Reaction - Garud, Dinesh R.; Rode, Navnath D.; Bathe, Sagar R.; Ranpise, Vinod S.; Joshi, Ramesh A.; Joshi, Rohini R.; Koketsu, Mamoru (Synthesis-Stuttgart, 2015)
The key N-homopropargylthiourea intermediates, N-substituted 2-oxo-4-propargylazetidine-1-carbothioamides, were prepared by the reaction of a 4-propargylazetidin-2-one with isothiocyanates. Bicyclic -lactams, i.e. 3-thia-1-dethiacephems, were prepared via highly regioselective iodocyclization reaction of N-substituted 2-oxo-4-propargylazetidine-1-carbothioamides with molecular iodine at room temperature in moderate to excellent yields. A variety of functional groups were well tolerated under the reaction conditions.
Keywords: -lactams; 3-thia-1-dethiacephems; Iodocyclization; Regioselective; thiourea

Synthesis and biological evaluation of 1,2,4-triazole-3-thione and 1,3,4-oxadiazole-2-thione as anti-mycobacterial agents - Sonawane, Amol; Rode, Navnath D.; Nawale, Laxman U.; Joshi, Rohini R.; Joshi, Ramesh A.; Likhite, Anjali P.; Sarkar, Dhiman (Chemical Biology & Drug Design, 2017)
Resistance among dormant mycobacteria leading to multi-drug resistant (MDR) and extremely-drug resistant(XDR) tuberculosis is one of the major threats. Hence, a series of 1,2,4-triazole-3-thione and 1,3,4-oxadiazole-2-thione derivatives (4a-5c) have been synthesised and screened for their anti-tubercular activity against Mycobacterium tuberculosis H37Ra (H37Ra). Thetriazolethiones4b and 4v showed high anti-tubercular activity (both MIC and IC50) against the dormant H37Ra by in vitro and ex vivo. They were shown to have more specificity towards mycobacteria than other gram-negative and gram- positive pathogenic bacteria. The cytotoxicity was almost insignificant up to 100 μg/mL against THP-1, A549 and PANC-1 human cancer cell lines, and solubility was high in aqueous solution, indicating the potential of developing these compounds further as novel therapeutics against tuberculosis infection.

Synthesis, biological evaluation, and molecular docking studies of novel 3-aryl-5-(alkyl-thio)-1H-1,2,4-triazoles derivatives targeting Mycobacterium tuberculosis - Rode, Navnath D.; Sonawane, Amol D.; Nawale, Laxman; Khedkar, Vijay M.; Joshi, Ramesh A.; Likhite, Anjali P.; Sarkar, Dhiman; Joshi, Rohini R. (Chemical Biology & Drug Design, 2017)
A small library of new 3-aryl-5-(alkyl-thio)-1H-1,2,4-triazoles was synthesized and screened for the antimycobacterial potency against Mycobacterium tuberculosis H37Ra strain and Mycobacterium bovis BCG both in active and dormant stage. Among the synthesized library, 25 compounds exhibited promising anti-TB activity in the range of IC(50)0.03-5.88g/ml for dormant stage and 20 compounds in the range of 0.03-6.96g/ml for active stage. Their lower toxicity (>100g/ml) and higher selectivity (SI=>10) against all cancer cell lines screened make them interesting compounds with potential antimycobacterial effects. Furthermore, to rationalize the observed biological activity data and to establish a structural basis for inhibition of M.tuberculosis, the molecular docking study was carried out against a potential target MTB CYP121 which revealed a significant correlation between the binding score and biological activity for these compounds. Cytotoxicity and in vivo pharmacokinetic studies suggested that 1,2,4-triazole analogues have an acceptable safety index, in vivo stability and bio-availability.